2014
DOI: 10.1038/srep05558
|View full text |Cite
|
Sign up to set email alerts
|

Developmental tuning of reflexive attentional effect to biological motion cues

Abstract: The human visual system is extremely sensitive to the direction information retrieved from biological motion. In the current study, we investigate the functional impact of this sensitivity on attentional orienting in young children. We found that children as early as 4 years old, like adults, showed a robust reflexive attentional orienting effect to the walking direction of an upright point-light walker, indicating that biological motion signals can automatically direct spatial attention at an early age. More … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 51 publications
2
30
0
Order By: Relevance
“…A previous study has demonstrated that the walking direction of BM cues can trigger a reflexive orienting effect ( Shi, Weng, He, & Jiang, 2010 ). This attentional effect can also be observed in preschool children and 6-month-old infants ( Bardi, Di Giorgio, Lunghi, Troje, & Simion, 2015 ; Zhao, Wang, Wang, Weng, Li, & Jiang, 2014 ). Such BM-induced attentional orienting effect persists even when the global configuration of BM is disrupted and observers are naïve to its biological nature ( L. Wang, Yang, Shi, & Jiang, 2014 ).…”
Section: Introductionmentioning
confidence: 73%
“…A previous study has demonstrated that the walking direction of BM cues can trigger a reflexive orienting effect ( Shi, Weng, He, & Jiang, 2010 ). This attentional effect can also be observed in preschool children and 6-month-old infants ( Bardi, Di Giorgio, Lunghi, Troje, & Simion, 2015 ; Zhao, Wang, Wang, Weng, Li, & Jiang, 2014 ). Such BM-induced attentional orienting effect persists even when the global configuration of BM is disrupted and observers are naïve to its biological nature ( L. Wang, Yang, Shi, & Jiang, 2014 ).…”
Section: Introductionmentioning
confidence: 73%
“…This leads to a difficulty with imitation (Vanvuchelen et al, 2013) and joint attention (Zhao et al, 2014), and has been regarded as one of the causes of the symptom A in Table 1.…”
Section: Mechanisms Cause Atypical Phenotypes Defined In Dsm-5mentioning
confidence: 99%
“…Studies focusing on biological motion demonstrate early emergence of this perceptual skill: even newborn babies show a preference for upright over inverted biological motion displays (e.g., Fox and McDaniel, 1982 ; Bertenthal et al, 1984 ; Simion et al, 2008 ), demonstrating their sensitivity to parameters that affect the perception of biological motion in adults (see Bertenthal et al, 1984 , for a discussion). Developmental studies beyond infancy, however, show that while 5-year-olds (Pavlova et al, 2000 ; Blake et al, 2003 ) and even 4-year-olds (Sweeny et al, 2013 ; Zhao et al, 2014 ) are as sensitive as adults to biological motion in displays without noise dots, substantial age-related change is seen in this sensitivity throughout childhood when the display includes moving noise dots (Pavlova et al, 2000 ; Jordan et al, 2002 ; Freire et al, 2006 ). When directly compared to global motion in the same participants with dots moving at the same speed, these skills of motion integration, for both RDKs measuring global motion and biological motion, show similar, long developmental trajectories (Hadad et al, 2011 ).…”
Section: Specific Cases Of Motion Integration: Biological Motion and mentioning
confidence: 99%